Rats pursue food and leisure following the same rational principles - Raegan S. Logue; Ana K. Garcia; Brissa A. Bejarano; Taylor Fujioka; Mikayla Duke; Riley K. Kendall; Andrew M. Wikenheiser (Proceedings of the National Academy of Sciences, 2025)
Animals in the wild must balance multiple, potentially mutually exclusive goals simultaneously in order to survive. Yet laboratory tests of decision-making often investigate how animals optimize their behavior to achieve a single, well-defined goal, which is often a nutritive reward. Thus, how animals solve multiobjective optimization problems is not well understood. Here, we devised an ethologically inspired decision-making task to examine how rats balance the pursuit of food and nonfood reinforcement. Rats performed a free-choice patch-foraging task, in which they could earn food in one location (food patch) or interact with a rodent play structure in a different location (toy patch). The cost of switching between patches was manipulated by requiring rats to endure a long or short “travel time” penalty during which they were not able to access either patch. Rats devoted a considerable amount of their limited foraging time to patches of both types, showing a small but significant preference for food patches. In accordance with theoretical models of foraging, when the cost of switching patches was high rats chose longer stay durations in both types of patches, suggesting that similar rational principles guided their pursuit of food and nonfood rewards. Examining the within-session dynamics of time allocation revealed that rats showed an early preference for spending time in toy patches that reversed over the course of the session. Satiety manipulations demonstrated that patch residence time decisions were under goal-directed control and responsive to current needs and recent consumption.